Communication Training Helps to Reduce Burnout During COVID-19 Pandemic - Katey Wert; Angela M Donaldson; Tri A Dinh; Daniel P Montero; Rebecca Parry; J Ross Renew; Daniel S Yip; Leigh Speicher (SAGE Publishing, 2023)
Objective To determine the effectiveness of communication training and its impact on burnout among healthcare providers (physicians, physician assistants, nurse practitioners), in the setting of the COVID-19 pandemic. Methods To evaluate the effectiveness of communication training on burnout during the COVID-19 pandemic, healthcare providers participating in a Communication in Healthcare (CIH) module between October 31, 2019, through February 20, 2020, were identified using a scanned sign-in sheet. A 3-question online survey regarding the utilization of communication skills during the COVID-19 pandemic was sent via email. An ordinal scale was used to rate the effectiveness of the training on subsequent burnout and work satisfaction during the pandemic. Results Of the 98 surveys distributed via email, a total of 33 participants completed the survey. Seventy-three percent of respondents agreed that communication training helped prevent burnout, and 39% strongly agreed that the modules improved work satisfaction. Conclusion Our study found communication training was effective in reducing burnout in healthcare providers, in the setting of the COVID-19 pandemic. The participants felt the communication tools learned from the training modules were useful in improving work satisfaction and communication with patients during the pandemic.